PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) DI KELAS IV C SDN PANDANWANGI 3 - Adelia, Nova; M Anas Thohir; Siti Amzah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study shows that the application of the Problem-Based Learning (PBL) learning model with a Culturally Responsive Teaching (CRT) approach can significantly improve the learning outcomes of students on the material of cultural diversity and local wisdom in class IVC SDN Pandanwangi 3. Learning that was originally teacher-centered and only relied on lectures and textbooks led to low active involvement of students and learning outcomes that were not optimal. This can be seen from the pre-cycle results which show that most students have not reached the Minimum Completeness Criteria (KKM). Through the application of the PBL model based on the CRT approach that accommodates students' cultural background and actively involves them in solving real problems, there is a significant improvement in learning outcomes. The percentage of learning completeness increased from 50% in cycle I to 82% in cycle II, with the average score increasing from 66.55 to 87.24. The findings prove that contextualized learning oriented to learners' culture can create a more inclusive, meaningful and effective learning experience in shaping 21st century skills and strengthening the learner profile of Pancasila.